LITERATUR REVIEW : DUKUNGAN SOSIAL BAGI ANAK DENGAN KEDISABILITASAN - Alfia Fadhila Husna; Hastin Trustisari (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Social support is crucial for the development of children with disabilities. Children with disabilities often face challenges such as negative stigma, social interaction difficulties, and self-care challenges. This study aims to analyze the forms of social support and its impact on the development of children with disabilities through a literature review. The method used is a descriptive literature review, searching Google Scholar for the keywords